Medical student mandala making for holistic well-being. Issue 1 (4th September 2015) - Potash, Jordan S; Chen, Julie Yun; Tsang, Joyce Pui Yan
Abstract : The objective of this qualitative research study was to discover how creating mandalas (art made in reference to a circle) might provide medical students with an opportunity for reflection on their current psychological state. As part of their year 3 family medicine rotation, medical students participated in an art-making workshop, during which, they created mandalas based on their current emotional state. Afterwards, they engaged in reflective writing and discussion. The responses of 180 students were analysed and coded according to the mandala classification framework 'Archetypal Stages of The Great Round of Mandala'. The results indicated that students were actively struggling in integrating conflicting perspectives as they were attempting to reconcile their professional identity as doctors. Additional results pertaining to psychosocial characteristics included navigating difficult emotions, requiring nurturance, handling endings, contemplating existential concerns and managing stress. The study has implications for making use of mandala making within a Jungian framework as means for medical students to reflect on their emotional state and achieve psychological balance.